Spectrophotometric Determination of Centrophenoxine Hydrochloride with Colour Reaction of Rose Bengal - Ma, Wei-Xing; Zhou, Yan; Ling Wang, Qiao; Zhang, Zheng (Asian Journal of Chemistry, 2012)
A new spectrophotometric method for determination of centrophenoxine hydrochloride was proposed based on the colour reaction of centrophenoxine hydrochloride with rose bengal to form ion association complex in the Clark-Lubs buffer media with pH 2.6, whose maximum wavelength was at 568 nm with the apparent molar absorptivity of complex was 5.589 × 103 L mol-1 cm-1, Beer law was obeyed in the range of 2-21 mg L-1 for centrophenoxine hydrochloride. The proposed method was stable, accurate, sensitive and rapid and has been applied for the determination of centrophenoxine hydrochloride with satisfactory results.